ISLAM KALANG: POLITIK IDENTITAS SUB ETNIS JAWA - Abdul Kholiq (Harmoni, 2013)
This research aims at studying the identity construction in Kalang, the identity formation of Islam-Kalang, and finally identity politics of the social and cultural life in Kalang. This research applies symbolic interaction and ethnographic approach because the study covers interpreting symbols. This research found that the identity attached to a people of Kalang was their blood identity. This identity affirms through the instrument of culture of Kalang, such as performing sayud, the ceremony of Obong, Gegalungan and the like. Throughout the history, the identity of Kalang had experienced some dynamics. Colonisation (Islam) occurred since the era of Demak (15th century). Despite resistance and difficult adaptation, they, eventually, accepted Islam. Islam becomes one of the most important identities, especially since 1966 when the government decided to ask its citizens to choose one of the official religions. The santri movement has been developed significantly in Sendangdawuhan due to the government political policy providing supportive space for the process of Islamisation since the 1990s. There have been some tendencies for fading the identity of Kalang due to the presence of Islam which then led to the presence of resistance as the political strategy to maintain their identity. The cosmological system in Kalang binding descendants of Kalang becomes the instrument of “defence” that can help people of Kalang to preserve their authentic identity. The other forms of resistance can be seen through the way they respect the spirit and adapt it to Islamic aspects through combined folklore between Islam and Kalang.